Implementation and evaluation of medical imaging techniques based on conformal geometric algebra - Franchini, Silvia; Gentile, Antonio; Vassallo, Giorgio; Vitabile, Salvatore (Zielona Góra: Uniwersytet Zielonogórski)
Medical imaging tasks, such as segmentation, 3D modeling, and registration of medical images, involve complex geometric problems, usually solved by standard linear algebra and matrix calculations. In the last few decades, conformal geometric algebra (CGA) has emerged as a new approach to geometric computing that offers a simple and efficient representation of geometric objects and transformations. However, the practical use of CGA-based methods for big data image processing in medical imaging requires fast and efficient implementations of CGA operations to meet both real-time processing constraints and accuracy requirements.
Keywords: medical image segmentation; medical image registration; computational geometry; Clifford algebra; conformal geometric algebra